Analysis of Sliding Characteristic of Traction Drive Reducer for Automotive In-wheel Motor - Shu Hongyu; Yao Zejie (Jixie chuandong)
To analyze the sliding characteristic of the traction drive reducer for the automotive in-wheel motor,the working mechanism is researched. Then,a mathematical model and an analysis method are proposed to accurately calculate the sliding characteristics combined with the elastohydrodynamic lubrication（ EHL） theory. Moreover,the relationships between the sliding rate and the transmission power are revealed,and the influences of the pressing force and the friction pair length on the sliding characteristics are discussed. The results show that,at a constant sliding rate,the increase in the pressing force can promote the viscosity and ultimate shear stress of the traction oils,improving the input and output powers; at a constant pressing force,with the increase in the sliding rate,the input and output powers first increase,and finally the input power tends to be stable while the output power decreases after reaching a peak; at a constant pressing force and a constant sliding rate,with the decrease in the inner or outer friction pair length,the input and output powers first increase and finally tend to a stable value respectively.